Two-year Functional Outcomes Of Operative Vs. Non-operative Treatment Of Completely Displaced Midshaft Clavicle Fractures In Adolescents: Results From A Prospective, Multicenter, Level 2 Study. Issue 7 (29th July 2019) - Heyworth, Benton E.; Pennock, Andrew T.; Li, G. Ying; Kalish, Leslie; Dragonetti, Brittany; Ellis, Henry B.; Nepple, Jeffrey J.; Willimon, S. Clifton; Spence, David; Pandya, Nirav K.; Kocher, Mininder S.; Edmonds, Eric W.; et al.
Objectives: To investigate the two-year functional outcomes and complications following operative versus non-operative treatment of completely displaced midshaft clavicle fractures in adolescents. Methods: All patients 10-18 years-old treated for a midshaft clavicle fracture between August, 2013 and August, 2018 at one of 8 geographically diverse, high-volume, tertiary-care pediatric centers were enrolled, with independent treatment decisions determined by individual providers. The sub-population of patients with completely displaced fractures was prospectively followed for over 2 years. Clinical course, complications, validated patient-reported outcome measures (PROs), quality of life metrics, and satisfaction scores were analyzed. To address the ceiling effect of the PRO/satisfaction data following clavicle injuries, a priori thresholds for 'suboptimal' scores were established (ASES scores <90, QuickDASH scores >10, EQ-5D <0.80). According to 'intention to treat' statistical principles, one post-operative complication (and a subsequent secondary operation) was analyzed within the non-operative cohort, given that the patient represented a 'crossover' from the non-operative to the operative treatment group. Results: Of the 909 patients enrolled in the prospective study, 417 patients (45.9%) demonstrated completely displaced fractures and maintained enrollment over the study period, 277 (66%) of whom had reached two year follow up, and 151 of whom provided adequate PRO data, representing a 55% response rate. Of these patients, 55 (36%) underwent operative treatment, while 96 (64%) were treated non-operatively. Those treated surgically showed no difference in gender distribution (76% males, p=0.43), athletic participation (p=0.76), or fracture pattern (p=0.18), but were older (mean age 15.3 vs. 13.5 years, p<0.001) and had greater shortening (p<0.001) than those treated non-operatively. Within the subset with adequate complication data, listed in Figure 1, complications were less common in non-surgical than surgical patients (p=0.0003), but this difference did not reach significance when sensory deficits were excluded (p=0.17). There was no difference in secondary surgeries (p=0.43). While greater percentages of operative than non-operative patients reported suboptimal PRO/satisfaction scores (ASES: 15% vs. 5%, QuickDASH 11% vs 5%, satisfaction 11% vs. 5%), these differences did not reach significance (p=0.07, 0.20, 0.06, respectively). Conclusion: At eight large pediatric centers with many surgeons making independent treatment decisions, non-operative treatment of adolescent clavicle fractures demonstrated lower complication rates and similar satisfaction and functional outcomes.These data establish a comprehensive functional assessment of adolescents treated for clavicle fractures, which represents the epidemiological sub-population most affected by this condition. Unlike several adult studies demonstrating superiority in operative treatment, this adolescent study demonstrates equivalent function and fewer complications associated with non-operative treatment. Complications of Completely Displaced Midshaft Clavicle Fractures with 2-Year Follow-Up Complication Surgical (N=53) Clinical Outcome Non-Surgical (N=87) Clinical Outcome p-value n (%) n (%) Hardware pain/irritation 5 (9.4%) 2 out of 5 (40%;3.8% overall): ROH surgery (mean 21.5 months post-op) 1 (1.1%) 'Crossover' patient: ORIF 2 months post-injury → ROH surgery 10 months post-op 0.03 Sensory symptoms 13 (24.5%) Numbness distal to incision (resolution reported in 5 out of 13, 38%, mean 6 months post-op) 1 (1.1%) Occasional paresthesias (6mo post-op) → spontaneous resolution <0.0001 Superficial Infection 0 (0.0%) 0 (0.0%) n/a Deep Infection 0 (0.0%) 0 (0.0%) n/a Delayed Union 2 (3.8%) Patient 1: bone stimulator (6 months post-op) → healing Patient 2: Revision ORIF → healed 2 (2.3%) Both patients: non-operative treatment → healed n/a Non-union 0 (0.0%) 0 (0.0%) n/a Symptomatic Malunion 0 (0.0%) 2 (2.3%) Patient 1: PT → improvement Patient 2: operative exostosis for bony prominence → resolution n/a Refracture 1 (1.9%) 2 wks following ROH → healed w/ non-operative tx 2 (2.3%) Both patients: non-operative treatment → healed n/a Other described below) 3 (5.7%) 0 (0.0%) n/a Atlanto-axial rotatory subluxation (immediately postoperative) 1 (1.9%) Unresponsive to halo traction → C1-2 fusion 0 (0.0%) n/a Intra-operative blood loss (1 liter) —* urgent vascular surgery consultation 1 (1.9%) Ligation of cephalic vein branch 0 (0.0%) n/a Development of acromioclavicular (AC) joint ganglion cyst (4 mo post-op) 1 (1.9%) US-guided AC joint aspiration, injection (7 mo post-op) # 0 (0.0%) n/a Any secondary operation 4 (7.5%) 3 (3.4%) 0.43 Any Complication 19 (35.8%) 8 (9.2%) 0.0003 Any Complication (excluding 'Sensory') 9 (17.0%) 7 (8.0%) 0.17 ROH = removal of hardware *PT = physical therapy # US = ultrasound